2017
DOI: 10.1002/bio.3387
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the luminescence properties of Sr3(PO4)2:Dy3+,Li+ white‐light‐emitting phosphors by charge compensator Li+ co‐doping

Abstract: Sr (PO ) :Dy ,Li phosphors were prepared using a simple high temperature solid method for luminescence enhancement. The structures of the as-prepared samples agreed well with the standard phase of Sr (PO ) , even when Dy and Li were introduced. Under ultraviolet excitation at 350 nm, the Sr (PO ) :Dy sample exhibited two emission peaks at 483 nm and 580 nm, which were due to the F → H and F → H transitions of Dy ions, respectively. A white light was fabricated using these two emissions from the Sr (PO ) :Dy ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, it can improve the asymmetry around the Eu 3+ location. 38,40,41 Thus, emission enhancement can be observed in R + -compensated samples. Furthermore, it is observed that Na + as a charge compensation corresponds to the highest luminous intensity.…”
Section: Spectral Characteristicsmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, it can improve the asymmetry around the Eu 3+ location. 38,40,41 Thus, emission enhancement can be observed in R + -compensated samples. Furthermore, it is observed that Na + as a charge compensation corresponds to the highest luminous intensity.…”
Section: Spectral Characteristicsmentioning
confidence: 98%
“…36 The addition of Li + , Na + , or K + ions to luminescent materials as charge compensation has been attracting considerable attention. 36–47…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…and are of great interest primarily due to their potential usage as efficient phosphors in light-emitting diode (LED) devices. 2 Among them phosphates such as calcium hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) and β-tricalcium diphosphate (Ca 3 (PO 4 ) 2 ) are used in implantology due to their high similarity to the inorganic bone tissues. These compounds activated with lanthanide ions are studied as bio-labels for in vitro and in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%